Romances of the republic : women, the family, and violence in the literature of the early American nation - Samuels, Shirley (OUP E-Books., 1996)
Samuels looks at the relations among sexual, political, and familial rhetoric in American writing from 1790 to the 1850s. With a special focus on the depictions of the American Revolution and the use of the family as model and instrument of political forces, she examines how the historical novel formalizes some of the more extravagant features of the gothic novel while incorporating a sentimental vision of the family.